Integrating religiosity with Technology Acceptance Model (TAM) and Technology Organization Environment (TOE) frameworks: A study on ICT adoption in micro and small enterprises - Dedy Setiawan; Junaidi; Jefri Marzal; Zulfanetti; Lucky Enggrani Fitri (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This study aims to develop an innovative TOE-TAM-Religiosity model that combines the TOE framework, TAM, and religious dimensions in adopting Information and Communication Technology (ICT) in organizations, especially micro and small businesses (SMEs). The TOE-TAM-Religiosity Model describes and analyzes the complex interactions between organizational factors, perceptions of technology, and religious values. Religion in this context refers to cultural and ethical values that influence individual and organizational attitudes towards applying technology. Influence user attitudes and intentions when adopting ICT. This research involved 399 respondents who were SMEs who were determined using the Slovin formula. To test the causal relationship of the data in this research using a PLS-based structural equation approach using the SmartPLS as an analysis tool. This research found a positive influence between technology, organization, environment, Religiosity, perceived usefulness (PU) and perceived ease of use (PEU) on ICT adoption. Furthermore, PU can bridge technology and ICT adoption, while PEU can be a bridge between organizations and ICT adoption. The results of this research can provide a framework and guidelines for SME management to improve their business performance after implementing ICT.
Keywords: 330; Technology organization environment; Technology acceptance model; religiosity; ICT adoption; MSEs; Perceived usefulness; Perceived ease of use